PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN INTERNAL DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KINERJA PEMERINTAH (Studi Empiris pada SKPD Kota Probolinggo Provinsi Jawa Timur) - Viola, Ima Reza; Andriana, Andriana; Wardhaningrum, Oktaviani Ari (Jurnal Riset Akuntansi Aksioma, 2023)
This research aimed to examine the clarity of budget targets, internal control and quality of human resources on the performance accountability of local government agencies in Probolinggo City. This study used a quantitative approach with primary data. The population are 18 government units in Probolinggo City. We used purposive sampling technique with some criteria applied, so that the sample we used are 100 respondents. The results of statistical tests show that the clarity of budget targets and the quality of human resources have a significant effect on government performance accountability, but internal control variables have no effect on government agency performance accountability in Probolinggo City’s government units.